2011
DOI: 10.1111/j.1582-4934.2011.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocytes derived from human embryonic and induced pluripotent stem cells: comparative ultrastructure

Abstract: Induced pluripotent stem cells (iPSC) are generated from fully differentiated somatic cells that were reprogrammed into a pluripotent state. Human iPSC which can be obtained from various types of somatic cells such as fibroblasts or keratinocytes can differentiate into cardiomyocytes (iPSC-CM), which exhibit cardiac-like transmembrane action potentials, intracellular Ca2+ transients and contractions. While major features of the excitation-contraction coupling of iPSC-CM have been well-described, very little is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 33 publications
(36 reference statements)
6
113
0
1
Order By: Relevance
“…Although peripheral couplings represent a landmark of cardiac muscle structure, signs of myocardiogenesis such as the presence of adhering structures ("primitive" intercalated disks) were not encountered in the present survey. Furthermore, in contrast to iPS-derived skeletal myocytes, cardiomyocytes display very few internal T-SR junctions (39) and no M-bands even after 4 mo in culture (40).…”
Section: +mentioning
confidence: 91%
“…Although peripheral couplings represent a landmark of cardiac muscle structure, signs of myocardiogenesis such as the presence of adhering structures ("primitive" intercalated disks) were not encountered in the present survey. Furthermore, in contrast to iPS-derived skeletal myocytes, cardiomyocytes display very few internal T-SR junctions (39) and no M-bands even after 4 mo in culture (40).…”
Section: +mentioning
confidence: 91%
“…It has been reported that early stage iPSC-CMs are small morphologically and exhibit an immature ultrastructure closely resembling that of fetal CMs (i.e., absence of T-tubules and underdeveloped contractile machinery). 42-44 However, upon prolonged culture, there were significant improvements in myofibril alignment, density and morphology showing adult-like appearance of Z disks, A-bands, I-bands and H-zones, although no clear M-bands or T-tubules were observed. 43, 44 Similarly, by combining bioengineering approaches with electrical stimulation, Nunes et al 45 developed a platform called ‘biowire’ that enables the generation of iPSC-CMs with ultrastructural properties similar to those seen in the native CMs.…”
Section: Ultrastructural Featuresmentioning
confidence: 98%
“…59 Indeed, iPSC-CMs exhibit a poorly developed SR and absence of T- tubules that likely affect their Ca 2+ handling properties. 42, 43 …”
Section: Excitation Contraction Coupling and Calcium Handlingmentioning
confidence: 99%
“…The latter feature is more accentuated in iPS-derived myocytes. Remarkably, iPS-derived myocytes lack gap junctions, intercalated disks, and T tubules (despite the presence of caveolae, considered precursors to T tubules) (28). However, studies in cardiomyocytes derived from human ESCs have demonstrated the presence of gap junctions (29).…”
Section: Ultrastructural Properties Of Ips-derived Myocytesmentioning
confidence: 99%